A new species of Hubera (Annonaceae) from Peninsular India - Ramachandran, Muralidharan; Narasimhan, Duvuru; Balachandran, Natesan (Phytotaxa, 2015)
Annonaceae, one of the most diverse plant families in tropical forests, comprise roughly 108 genera and 2400 species (Rainer et al. 2006, Chatrou et al. 2012). As per the current understanding, Annonaceae have four subfamilies: Anaxagoreoideae, Ambavioideae, Annonoideae and Malmeoideae (Chatrou et al. 2012). Phylogenetic studies on Annonaceae (Mols et al. 2004; Erkens et al. 2007; Su et al. 2008; Nakkuntod et al. 2009; Chatrou et al. 2012) have brought significant changes in circumscription and nomenclature of several genera due to the strict adherence to the principle of monophyly (Su et al. 2005, 2010; Rainer, 2007; Mols et al. 2008; Saunders, 2009; Chaowasku et al. 2011, 2012; Xue et al. 2012, 2014). The problematic case of the polyphyletic genus Polyalthia Blume s.l. (1830: 68) has recently been studied phylogenetically in detail and presently is fully solved; species of Polyalthia s.l. have been segregated into several smaller monophyletic genera, for example, Fenerivia Diels (1925: 355; Saunders et al. 2011), Hubera Chaowasku (2012: 46; Chaowasku et al. 2012), Maasia Mols, Keßler  & Rogstad (2008: 493; Mols et al. 2008), Marsypopetalum Scheffer (1870: 342; Xue et al. 2011) and Monoon Miquel (1865: 15; Xue et al. 2012).